EZH2 Expression in Head-and-Neck Squamous Cell Cancer in Young Patients - Révész, Mónika; Oberna, Ferenc; Slezák, András; Tóth, Erika; Ferenczi, Örs; Kenessey, István; Takácsi-Nagy, Zoltán (International journal of molecular sciences, 2024)
EZH2 (Enhancer of zeste homolog 2) promotes tumor growth and survival through numerous mechanisms and is a promising target for novel therapeutic approaches. We aimed to characterize the expression of EZH2 in the tumors of young head-and-neck squamous cell cancer (HNSCC) patients in comparison with the general HNSCC patient population. We used formalin-fixed, paraffin-embedded tissue blocks from 68 random young HNSCC patients (≤39 years, median age: 36 years; diagnosed between 2000 and 2018), which were compared with the samples of 58 age- and gender-matched general HNSCC subjects (median age: 62 years; all diagnosed in the year 2014). EZH2 and p53 expression of the tumors was detected using immunohistochemical staining. Lower EZH2 expression was found to be characteristic of the tumors of young HNSCC patients as opposed to the general population (median EZH2 staining intensity: 1 vs. 1.5 respectively, p < 0.001; median fraction of EZH2 positive tumor cells: 40% vs. 60%, respectively, p = 0.003, Mann–Whitney). Cox analysis identified a more advanced T status (T3-4 vs. T1-2), a positive nodal status, and alcohol consumption, but neither intratumoral EZH2 nor p53 were identified as predictors of mortality in the young patient group. The lower EZH2 expression of young HNSCC patients’ tumors discourages speculations of a more malignant phenotype of early-onset tumors and suggests the dominant role of patient characteristics. Furthermore, our results might indicate the possibility of an altered efficacy of the novel anti-EZH2 therapies in this patient subgroup.